Performances of SBS and Nano-TiO2 composite modified asphalt and mixture after repetitive aging and regeneration - Fan, Xuefeng; Shan, Gang; Fan, Jianwei; Tang, Fanlong (Frontiers in Materials, 2025)
The long-term durability of SBS–nano TiO2 composite modified asphalt and mixtures is affected by repetitive aging and regeneration, which alter their mechanical and environmental performance. Understanding these changes is critical for improving the recycling and reuse of modified asphalt in pavement engineering. In this study, SBS–nano TiO2 composite modified asphalt underwent primary aging, primary regeneration, secondary aging, and secondary regeneration. Micro-scale tests, including gel permeation chromatography (GPC) and scanning electron microscopy (SEM), were conducted to assess morphological and molecular weight changes. Macro-scale performance tests, including dynamic shear rheometer (DSR), bending beam rheometer (BBR), rutting, bending, Marshall stability, splitting strength, and dynamic modulus tests, were used to evaluate high- and low-temperature properties, moisture resistance, and fatigue resistance. The results showed that repeated aging caused SBS degradation, reducing its molecular weight, while oxidation of asphalt components increased their molecular weight. In regenerated asphalt, aged and cracked SBS chains interwove with newly added chains, whereas nano-TiO2 remained stable throughout aging and regeneration. High-temperature performance of asphalt and mixtures was significantly enhanced after aging, but low-temperature properties and fatigue resistance deteriorated. Regeneration partially restored these properties, though not to the level of the original material. Moisture resistance remained generally stable, with freeze–thaw splitting strength ratio decreasing by 3.3%–4.1%. The dynamic modulus increased with aging but declined after regeneration, while fatigue resistance showed the opposite trend. Overall, SBS–nano TiO2 composite modified asphalt and mixtures exhibit superior high-temperature performance compared to the original material after repeated aging and regeneration. However, their low-temperature and fatigue properties decline progressively. Regeneration mitigates but cannot fully reverse these effects. These findings provide a performance basis for the repeated recycling of composite modified asphalt and highlight the need for strategies that better restore low-temperature and fatigue performance during regeneration.